AWS certified developer-associate (DVA-C01) cert guide - Sluga, Marko (Expert on cloud computing) (Pearson IT Certification, 2020)
The AWS Certified Developer Associate certification demonstrates your expertise in developing, deploying, and maintaining applications on the world's leading cloud platform, Amazon Web Services. AWS Certified Developer Associate Cert Guide is the comprehensive self-study resource for the updated version of Amazon's valuable new exam. Designed for all AWS Certified Developer Associate candidates, this guide covers every exam objective concisely and logically, with extensive teaching features designed to promote retention and understanding. You'll find: Hands-on labs you can perform with a free AWS account Real-world examples throughout Pre-chapter quizzes to assess knowledge upfront, and efficiently focus your study Foundation topics sections that explain concepts and configurations, and link theory to practice Key topics sections calling attention to every figure, table, and list you must know Exam Preparation sections with additional chapter review features Final preparation chapter with tools and resources to help you craft review and test-taking strategies and optimize study time A customizable practice test library This guide's comprehensive, developer-focused, real-world coverage addresses all exam topics related to: AWS authentication, identity and access management Computing services Data storage, processing, and transformation AWS developer tools DevOps: CI/CD in the cloud AWS Cloud9 and CodeStar Migrating, refactoring, monitoring, and troubleshooting AWS code.